Pharmacognostical and Pharmaceutical Assay of Balachaturbhadra churna A Compound Ayurvedic Formulation - Joshi, Abhishek (International Journal of Pharmaceutical & Biological Archive, 2013)
Pharmacognostical and Pharmaceutical Assay of Balachaturbhadra churna A Compound Ayurvedic Formulation